Rapid Monitoring of Mercury in Air from an Organic Chemical Factory in China Using a Portable Mercury Analyzer - Akira Yasutake; Jin Ping Cheng; Masako Kiyono; Shimpei Uraguchi; Xiaojie Liu; Kyoko Miura; Yoshiaki Yasuda; Nikolay Mashyanov (The Scientific World Journal)
A chemical factory, using a production technology of acetaldehyde with mercury catalysis, was located southeast of Qingzhen City in Guizhou Province, China. Previous research showed heavy mercury pollution through an extensive downstream area. A current investigation of the mercury distribution in ambient air, soils, and plants suggests that mobile mercury species in soils created elevated mercury concentrations in ambient air and vegetation. Mercury concentrations of up to 600 ng/m3 in air over the contaminated area provided evidence of the mercury transformation to volatile Hg(0). Mercury analysis of soil and plant samples demonstrated that the mercury concentrations in soil with vaporized and plant-absorbable forms were higher in the southern area, which was closer to the factory. Our results suggest that air monitoring using a portable mercury analyzer can be a convenient and useful method for the rapid detection and mapping of mercury pollution in advanced field surveys.